2019
DOI: 10.1155/2019/6708474
|View full text |Cite
|
Sign up to set email alerts
|

Early Lymph Node Metastasis May Predict Poor Prognosis in Soft Tissue Sarcoma

Abstract: Background. Lymph node metastasis (LNM) is a relatively rare event in soft tissue sarcoma. An association between the timing of LNM detection and patient prognosis is presently unknown. Patients and Methods. We retrospectively analyzed the clinicopathological features of 33 patients with LNM between 2001 and 2015. Analysis of the timing of LNM diagnosis was grouped according to patients presenting LNM in either <8 months (the median time from primary tumor diagnosis to LNM) or ≥8 months after primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Some potential explanations are that changes in tumor size may be closely related to its biological behavior and LNM is regarded as a prerequisite for malignant tumor invasion and metastasis. 30 , 31 David et al also supported the notion that lymph node positivity is a predictive sign of biological aggressiveness and distant metastasis. 32 Taken together, STS patients with the characteristics of higher grade, histologic type of synovial sarcoma, LNM, and tumor size larger than 10 cm were associated with increased risk of LM at initial diagnosis and justified more thorough chest computer tomography scanning.…”
Section: Discussionmentioning
confidence: 88%
“…Some potential explanations are that changes in tumor size may be closely related to its biological behavior and LNM is regarded as a prerequisite for malignant tumor invasion and metastasis. 30 , 31 David et al also supported the notion that lymph node positivity is a predictive sign of biological aggressiveness and distant metastasis. 32 Taken together, STS patients with the characteristics of higher grade, histologic type of synovial sarcoma, LNM, and tumor size larger than 10 cm were associated with increased risk of LM at initial diagnosis and justified more thorough chest computer tomography scanning.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the low incidence, the confirmation of LNM seems to be a clinical expression of the biological aggressiveness of the STS, patients with LNM are prone to have unsatisfactory survival outcome ( 6 ). The 5-year survival for patients with STS with LNM is reported to range from 12.5% to 45.5% ( 7 , 8 ), similar to the 5-year overall survival (OS) rate in patients with oligometastatic disease localized to the lungs, which is estimated to be approximately 25% to 40% ( 9 ). Because of the dismal prognosis, patients with LNM would be considered to be in the advanced stage of the disease.…”
Section: Introductionmentioning
confidence: 83%
“…Upon univariate analysis, negative prognostic factors for metastasis included T-score, tumor size, LN involvement, LVI, local recurrence, and tumor location. 27,43,44 Multivariate analysis revealed that tumor size ≥7 cm, LN involvement, and LVI all led to more than twofold increases in the risk of metastasis. This implies that patients with increased tumor size, nodal involvement, and vascular invasion had worse clinical outcomes (Table 3, Figures 1B and 3).…”
Section: Discussionmentioning
confidence: 99%